The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/14651858.cd003976.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological interventions for pain relief during orthodontic treatment

Abstract: Analgesics are more effective at reducing pain following orthodontic treatment than placebo or no treatment. Low-quality evidence did not show a difference in effectiveness between systemic NSAIDs compared with paracetamol, or topical NSAIDs compared with local anaesthetic. More high-quality research is needed to investigate these comparisons, and to evaluate pre-emptive versus post-treatment administration of analgesics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 44 publications
2
31
0
3
Order By: Relevance
“…Assessing these aspects with remote controls is complicated. Pain during orthodontic treatment that arises at specific stages of device activation, somehow predictable in advance, can be treated pharmacologically safely and effectively [26].…”
Section: Discussionmentioning
confidence: 99%
“…Assessing these aspects with remote controls is complicated. Pain during orthodontic treatment that arises at specific stages of device activation, somehow predictable in advance, can be treated pharmacologically safely and effectively [26].…”
Section: Discussionmentioning
confidence: 99%
“…A suggested medication is anti-inflammatory drugs and muscle relaxants such as nonsteroidal anti-inflammatory drugs to ease pain and swelling in the acute phase. 17 …”
Section: Suggestions For Acute Musculoskeletal Pain Management Durmentioning
confidence: 99%
“…56 The role of pre-emptive analgesia for the pain experienced when undergoing orthodontic treatment was explored as part of a recent Cochrane Systematic Review. 57 The authors found that using pre-emptive ibuprofen one hour before separator placement reduced pain intensity at two…”
Section: Pre-emptive Analgesiamentioning
confidence: 99%